1987
DOI: 10.1002/art.1780300805
|View full text |Cite
|
Sign up to set email alerts
|

Plasma from rheumatoid arthritis patients does not contain abnormally high levels of α2‐macroglobulin–proteinase complexes

Abstract: We measured the levels of az-macroglobulin (azM)-proteinase complexes in the plasma of 18 patients with classic rheumatoid arthritis, 11 age-matched patients with noninflammatory back pain and osteoarthritis, and 8 healthy volunteers. In contrast with previous reports, we found no evidence of a2M-proteinase complexes in the plasma samples from individuals in any of the groups. In our assays, all activity that might have been the result of the presence of such complexes in the plasma samples proved instead to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
1993
1993

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Preparation of a-macroglobulin. a2-Macroglobulin was generously given by Dr. M. E. Davies of this laboratory and was purified from fresh human plasma by poly(ethylene glycol) precipitation, zinc chelate affinity chromatography and gel filtration with Ultrogel AcA-34 as described by Davies et al (1987). Analysis on non-SDS/5 %-(w/v)-polyacrylamide gels showed that the protein was all the electrophoretically slow form of a2macroglobulin (Barrett et al, 1979).…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of a-macroglobulin. a2-Macroglobulin was generously given by Dr. M. E. Davies of this laboratory and was purified from fresh human plasma by poly(ethylene glycol) precipitation, zinc chelate affinity chromatography and gel filtration with Ultrogel AcA-34 as described by Davies et al (1987). Analysis on non-SDS/5 %-(w/v)-polyacrylamide gels showed that the protein was all the electrophoretically slow form of a2macroglobulin (Barrett et al, 1979).…”
Section: Methodsmentioning
confidence: 99%